Percutaneous Reduction of Displaced Radial Neck Fractures Achieves Better Results Compared With Fractures Treated by Open Reduction. Issue 4 (June 2016) - Shabtai, Lior; Arkader, Alexandre
Abstract : There is uniform agreement in the literature that radial neck fracture with <30 degrees of angulation and minimal translation in younger children can be managed by casting alone, without the need for closed reduction. For more severe fractures, closed manipulation techniques followed by percutaneous reduction technique (in case closed reduction fails) should be performed before switching to an open reduction technique. Debate still exists regarding the best treatment protocol for severely displaced fractures. Although some surgeons favor open reduction with the argument that repeat manipulations may cause iatrogenic injuries, and stiffness, others believe that open reduction is one of the most contributing factors for poor outcome. On the basis of this paradigm, we present our treatment algorithm based on the data demonstrating that percutaneous reduction of displaced radial neck fractures achieve better results than open reduction.